Financial Literacy And Investment Interest In Islamic Students: Literasi Keuangan dan Minat Berinvestasi pada Mahasiswa Islam - Maulidiyah , Eva Dwi; Nirwana, Nihlatul Qudus Sukma (Universitas Muhammadiyah Sidoarjo, 2025)
Background: The development of Islamic capital markets has increased interest among students to invest, yet their understanding of financial literacy remains limited. Specific Background: Previous studies focused mainly on conventional literacy, while this research emphasizes Islamic financial literacy among students. Knowledge Gap: There is a lack of empirical data linking Islamic financial literacy with students’ investment interest. Aims: This study aims to identify the level of Islamic financial literacy and its relationship with students’ investment interest. Results: Findings indicate that students with higher literacy levels demonstrate stronger interest and better investment behavior aligned with sharia principles. Novelty: This study integrates financial education and Islamic values as an approach to strengthening students’ economic awareness. Implications: The results suggest that universities should enhance Islamic financial literacy through curriculum integration and practical exposure to sharia-compliant financial activities. Highlights:• Islamic financial literacy enhances students’ investment awareness• Integration of Islamic values in financial learning• Educational implication for Islamic higher education Keywords: Islamic financial Literacy, Investment Interest, Students, Sharia Education, Islamic Economics